Optimasi Metoda Isolasi Katekin dari Gambir Untuk Sediaan Farmasi dan Senyawa Marker - Rahmawati, Noveri; Bakhtiar, Amri; Putra, Deddi Prima (Jurnal Sains dan Teknologi Farmasi, 2011)
Optimization studies out on isolation of catechin from gambier and pasta for the pharmaceutical and marker compounds have been carried. Gambier gambier and paste were obtained from the Medicinal Plant Garden Andalas University, Siguntur and Lima Puluh Kota. Isolation method used was non-purification method, pre-purification for gambier and fractination for pasta. The analysis performed included catechin solubility, melting point, maximum absorption, thin-layer chromatography, loss on drying, ash content, yield and determination of levels of catechin. Product which has the highest levels of catechins, the determination was continued by analysis of UV spectra and NMR. The best results for pharmaceuticals derived from Siguntur with pre-purification methods which resulted in yield 56.3% with 96.17% catechin content, whereas for a marker compound was obtained from gambier Siguntur pasta with fractionation method which yielded 12.13% with 97.96% of catechin level.